Failure mechanism of glass-fiber reinforced laminates influenced by the copper film in three-point bending. (August 2018) - Hou, Pengliang; Zhao, Anran; Wu, Weidong; Huan, Haixiang; Li, Cong; Wang, Shunbo; Zhao, Hongwei
Abstract: In this paper the influence of copper film on the stress distribution, damage evolution and failure mechanism of glass-fiber reinforced laminates was investigated. The specimens were tested at the in situ three-point bending tester. Simultaneously, a microscope and acoustic emission (AE) system were applied to in situ characterize the damage evolution of surface and inside of specimens, respectively. Moreover, a finite element analysis (FEA) model was constructed to simulate the stress distribution on the different types of specimens during the three-point bending. The result of the finite element simulation was in agreement with that of the experiment. The bending stress distribution on the specimen of glass-fiber reinforced laminates (no copper film) and double-sided copper-clad laminates was different from that of the single-sided copper-clad laminates, which made the failure mechanism of single-sided copper-clad laminates was not the same as the glass-fiber reinforced laminates and double-sided copper-clad laminates. It is obviously that the copper film can effectively improve the mechanical properties of glass-fiber reinforced laminates. The in situ images revealed the damage evolution of glass-fiber reinforced laminates and single-sided and double-sided copper-clad laminates was not the same. Furthermore, the glass-fiber fracture, the glass-fiber stripping from the substrate and matrix cracking were characterized by the amplitude, count, rise time, duration time, energy of AE signals during the three-point bending.